2020
DOI: 10.1108/mbe-07-2019-0071
|View full text |Cite
|
Sign up to set email alerts
|

Development of employee engagement measure: experiences from best companies to work for in India

Abstract: Purpose Employee engagement has become a hot topic among the global workforce. Both academicians and practitioners tout engagement to have a positive impact on individual and organizational performance. However, despite the enhanced interest, the stagnant engagement levels worldwide pose a grave concern for the researchers. Numerous overlapping and inconsistent definitions of employee engagement lead to a conceptual chaos resulting in poor operationalization of the construct. The purpose of this paper is to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Second, literature and studies concerning empowering and ethical leadership in the organization field are still limited. The result from this study uncovers the relationship among variables that have been neglected in preliminary studies (Mwesigwa et al, 2020;Nazir et al, 2021;Shrotryia & Dhanda, 2020). It can better understand the factors that affect employees' job satisfaction to their performance and commitment.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Second, literature and studies concerning empowering and ethical leadership in the organization field are still limited. The result from this study uncovers the relationship among variables that have been neglected in preliminary studies (Mwesigwa et al, 2020;Nazir et al, 2021;Shrotryia & Dhanda, 2020). It can better understand the factors that affect employees' job satisfaction to their performance and commitment.…”
Section: Introductionmentioning
confidence: 82%
“…In some cases, managers and companies focus more on profit-making than employees' well-being, enhancing dissatisfaction (Coggburn, Paul, & Mark, 2017;Sharma et al, 2019;Valaei & Rezaei, 2016). Studies have concluded that personal psychology has a crucial role in addressing the correlation between employees' job satisfaction and job engagement (Dhamija, Gupta, & Bag, 2019;Håvold, Håvold, & Glavee-Geo, 2021;Shrotryia & Dhanda, 2020).…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees with high engagement levels are more creative (Bakker and Demerouti, 2008), exhibits high task performance (Shuck and Wollard, 2010; Soane et al , 2012), are easy to retain (Saks, 2006) and leads to better financial implications for the organisation (Nayar, 2010; Hewitt, 2013). However, despite the increased awareness and known benefits, organisations worldwide fail to increase their employee engagement levels (Shrotryia and Dhanda, 2020) and reap its benefits (Shuck et al , 2016). In their study, Mann and Harter (2016) reported that only 13% of the world’s working population is currently engaged.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this study is the first to explore the relationship between the various dimensions of EE and OCB. For this study, we use a more comprehensive definition of EE including the three facets of alignment, affectiveness and action-orientation (Shrotryia and Dhanda, 2020b). This inter-relationship enables us to disentangle the effect of different facets of EE on OCB.…”
Section: Introductionmentioning
confidence: 99%